دور المصارف الخضراء في تحقيق أبعاد التنمية المستدامة دراسة تجارب - نجاة التجاني; جميلة بن طرية (جامعة الوادي university of eloued, 2024)
"الملخص تهدف هذه الدراسة إلى التعرف على المصارف الخضراء التي تلتزم بتطبيق الممارسات الصديقة للبيئة و تمويل المشاريع الخضراء لدعم التنمية المستدامة من خلال ثلاث أبعاد رئيسية ، و هذا بتكييف خدماتها و سياساتها المصرفية بما يدعم المشاريع و الاستثمارات الصديقة للبيئة، تساعد هذه الاستثمارات على التقليل من البصمة الكربونية وتحقيق التوازن البيئي وتساعد على خلق فرص عمل و تعزيز الابتكارات في التقنيات النظيفة و تحقيق العدالة الاجتماعية و قد شرعت العديد من المصارف حول العالم في دعم و مسايرة هذا التوجه ، تبعتها في ذلك العديد من المصارف العربية و من بينها الجزائر، والتي شرعت في تعزيز الخدمات و الأنشطة المصرفية التي تتماشى و اهداف و متطلبات أبعاد التنمية المستدامة وتشير الدراسات أن توجه الدول العربية يتعرض إلى تحديات و عقبات تحتاج إلى سبل لتطويرها. " "Abstract: This study aims to identify green banks that are committed to applying environmentally friendly practices and financing green projects to support sustainable development through three main dimensions, by adapting their services and banking policies to support environmentally friendly projects and investments. These investments help reduce the carbon footprint, achieve environmental balance, and help create job opportunities, promote innovations in clean technologies, and achieve social justice. Many banks around the world have begun to support and keep pace with this trend, followed by many Arab and international banks. Among them is Algeria, Which has begun to enhance banking services and activities that are consistent with the goals and requirements of the dimensions of sustainable development. Studies indicate that the trend of Arab countries is exposed to challenges and obstacles that require ways to develop them."
Keywords: المصارف الخضراء، التنمية المستدامة، تجارب دولية; green banks; sustainable development; international experiences